Symptomatic management of neurodegenerative disease in the elderly. (2nd January 2017) - Oliver, David J.; Veronese, Simone
Abstract : The care of elderly people with progressive neurodegenerative disease is often complex and palliative care may be helpful from soon after diagnosis to enable the quality of life to be maintained as much as possible. Palliative care may be involved in an episodic way, as new problems and issues are faced, throughout the disease progression. There are many issues which require careful assessment, including symptoms, psychological, and social aspects of care. This may include the assessment of cognitive change and ensuring that symptoms and issues are addressed correctly, even if the person cannot communicate or is cognitively compromised. This care will also include carers, spouses and families, professional carers, and carers within residential and nursing homes. Patients and carers may need ongoing support, to cope with the multiple and continual losses faced within neurological disease progression, with the complex interaction with other comorbidities and the effects of ageing. As the progression continues the recognition of end of life, through the assessment of triggers, is important so that all can be prepared for dying and death.